State of Climate Change Adaptation and Mitigation Efforts for Agriculture in Burkina Faso - Samari, H. (2011)
Burkina Faso epitomizes the increasing concerns over food security in the Sahel region. Over the past three decades, the country has gone through a series of natural calamities marked by droughts and flooding, which negatively impacted crop production and greatly increased concerns over food supply. This vulnerability of the country to climate change has led successive governments and policymakers to seek solutions through various initiatives. As a country whose economy and sociopolitical stability strongly depend on the primary sector – Burkina Faso is a regional powerhouse for cotton production and exports – Burkina Faso has indeed been proactive in tackling environment-related issues within its borders and across the region. These ongoing efforts are far from solving the entire problem, however. Serious material and financial limitations as well as technical and technological handicaps are still preventing the country from fully achieving its set goals.